Phenotypic clusters and biomarkers profile in patients with chronic heart failure with preserved and mildly reduced left ventricular ejection fraction - Natalia A. Dragomiretskaya; Anastasia V. Tolmacheva; Alexander A. Ivannikov; Ilya I. Shvedov; Artyom V. Belyakov; Kamila R. Agalarova; Valery I. Podzolkov (Терапевтический архив)
Aim. To study the profile of cardiac biomarkers (NT-proBNP – N-terminal pro-brain natriuretic peptide, sST2 – soluble growth stimulation expressed gene 2, galectin-3, copeptin) in clusters of patients with chronic heart failure with preserved (CHFpEF) and mildly reduced (CHFmrEF) left ventricular (LV) ejection fraction (EF).